Successful treatment by exchange transfusion of a young infant with sodium nitroprusside poisoning - Jong Geun Baek; Hoar Lim Jeong; Ji Sook Park; Ji Hyun Seo; Eun Sil Park; Jae Young Lim; Chan Hoo Park; Hyang Ok Woo; Hee Shang Youn; Jung Sook Yeom (Korean Pediatric Society, 2010)
Although sodium nitroprusside (SNP) is often used in pediatric intensive care units, cyanide toxicity can occur after SNP treatment. To treat SNP-induced cyanide poisoning, antidotes such as amyl nitrite, sodium nitrite, sodium thiosulfate, and hydroxycobalamin should be administered immediately after diagnosis. Here, we report the first case of a very young infant whose SNP-induced cyanide poisoning was successfully treated by exchange transfusion. The success of this alternative method may be related to the fact that exchange transfusion not only removes the cyanide from the blood but also activates detoxification systems by supplying sulfur-rich plasma. Moreover, exchange transfusion replaces cyanide-contaminated erythrocytes with fresh erythrocytes, thereby improving the blood's oxygen carrying capacity more rapidly than antidote therapy. Therefore, we believe that exchange transfusion might be an effective therapeutic modality for critical cases of cyanide poisoning.